Interpersonal relationships and depression among adolescents living in Tehran's shelters - Ahangar, Katayoon; Mansor, Mariani; Juhari, Rumaya (University of Victoria, 2012)
This report explores the connection between interpersonal relationships and depression among adolescents living in Tehran’s shelters. A total 103 Iranian adolescents from nine governmental shelters in Tehran, comprising 69 males and 34 females between the ages of 13 and 15 years, were included in this research. A correlational design was employed in this study and a convenience sampling method was used to select respondents. The results revealed significant negative correlations for depression and difficulties with interpersonal relationships with roommates, classmates, social workers, and guardians. The results of this study will help guardians, social workers, and psychologists to organize intervention programmes that assist with relationship formation as a means for reducing depression among adolescents in Tehran’s youth shelters.